Studies of in vitro anti-prostate cancer potential of newer 1,2,4-triazolo-1,3,4-thiadiazines with different heteroaromatics (Bangladesh Journal of Pharmacology, 2015)
This study was aimed to evaluate anticancer potential of newer synthesize 1,2,4-triazolo[3,4-b]-1,3,4-thiadiazines and its derivatives. All newly furnished scaffolds were subjected to screening for their in vitro anticancer potential against DU-145 and PC-3 prostate cancer cell lines using SRB and MMT bioassays. The structures of final compounds were confirmed with the aid of FT-IR, 1H NMR, 13C NMR spectroscopy and CHN analysis. Bioassay studies suggested that all thiadiazines were promising cytotoxic agents with % cytotoxicity ranging from 44.39-71.24%, whereas potent GI50 level in the range 11.96-32.51 µg/mL and results were comparable to the potencies of control drugs adriamycin and doxorubicin. Variation of heterocyclic pharmacophores along with the C-5 position of 1,2,4-triazole in terms of quinoline, quinazoline, coumarin and pyridine lead to the different SAR predictions in which quinoline and benzimidazole moieties found most promising.